Effect of invasive tests during pregnancy on perinatal transmission of hepatitis B infection: a scoping review - Ka Wang Cheung; Tiffany Sin-Tung Au; Ying Rong Li; Zhenyan Han; Zhu Zhang; Mimi Tin Yan Seto (EClinicalMedicine)
Summary: Prenatal and intrapartum invasive tests are possible mechanisms of mother to child transmission (MTCT) of hepatitis B virus (HBV). The viral activity can affect the MTCT risk after invasive tests, but the evidence is scarce. This scoping review discussed the effects of prenatal or intrapartum invasive tests on the risk of HBV MTCT. The risk of MTCT after amniocentesis was low among hepatitis B infected pregnant individuals with negative hepatitis B e antigen (HBeAg) statuses or HBV DNA < 7 log10 IU/mL, and comparable to those that did not undergo prenatal invasive tests. Amniocentesis could increase the risk of MTCT among women with seropositive HBeAg statuses or HBV DNA ≥ 7 log10 IU/mL, but there were no MTCT among these women who received antiviral treatment. Data on CVS, cordocentesis and intrapartum invasive tests were insufficient to conclude their effects on MTCT. We also reviewed 50 international clinical practice guidelines. Most of them did not have recommendations on the management of hepatitis B infected pregnant individuals requiring prenatal or intrapartum invasive tests and significant discrepancies existed among the remaining guidelines. A workflow and two pragmatic approaches were discussed to assist clinical management. Furthermore, we would like to encourage future research to provide comprehensive data on the factors influencing the MTCT rate (such as maternal HBV DNA viral load and HBeAg status, availability and timing of neonatal birth dose immunizations, transplacental or transamniotic invasive tests, complications of the invasive tests and the use of antiviral prophylaxis).